2019
DOI: 10.3390/ani9060297
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sweet Potato Vine on the Onset of Puberty and Follicle Development in Chinese Meishan Gilts

Abstract: This study was conducted to evaluate the effects of sweet potato vine on the onset of puberty and the follicular development in the ovaries of Chinese Meishan gilts. A total of 20 Meishan gilts (initial body weight at 30 ± 0.18 kg) were randomly fed a control (CON) or sweet potato vine (SPV) supplemented diet until 19 days following the third estrous. Sweet potato vine was instead of part of basal diet with the same amount of energy and protein in the sweet potato vine group. The results indicate that gilts fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 37 publications
4
8
0
Order By: Relevance
“…Consistent with these results, we also found that SPV treatment increased non-esterified fatty acid in the plasma as well as fatty acid catabolism gene expression level of CPT-1 and PPAR-α in the liver. Such results support our previous research that gilt in the SPV treatment reached puberty 9.4 days later than those in the CON treatment [1]. Previous studies have proposed that puberty occurs only after the attainment of a minimum level of leanness or fatness, or ratio of fat to lean [24].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Consistent with these results, we also found that SPV treatment increased non-esterified fatty acid in the plasma as well as fatty acid catabolism gene expression level of CPT-1 and PPAR-α in the liver. Such results support our previous research that gilt in the SPV treatment reached puberty 9.4 days later than those in the CON treatment [1]. Previous studies have proposed that puberty occurs only after the attainment of a minimum level of leanness or fatness, or ratio of fat to lean [24].…”
Section: Discussionsupporting
confidence: 90%
“…Gilts were housed in individual stalls, and each gilt was one replicate. The animals as well as their basal diets, feeding regime, and treatments were the same as those found in our previous study [1]. Briefly, basal diet included 3.08 Mcal DE /kg, 14.00% of CP, 0.68% Lysine, 0.53% calcium, and 0.48% phosphorus.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies indicated the extend biological impacts of sweet tastants on animals, purple sweet potato could enhance the immune response after immunization in chickens (Hanieh et al, 2010), dietary sweet orange peel extract might improve the immune response and diseases resistance in broiler feeding (Pourhossein et al, 2015), and sweet potato vine supplementation delayed puberty onset (Zhang et al, 2019) and promoted intestinal muscle development (Xu et al, 2019) in Chinese Meishan gilts. However, exposure to sweet tastants is likely to lead to physiological consequences as T1R2 and T1R3…”
mentioning
confidence: 99%